Solar sailing CubeSat attitude control method with satellite as moving mass. (June 2019) - Huang, He; Zhou, Jun
Abstract: Low-cost solar sailing CubeSats for deep-space exploration are relatively inexpensive, have a short development time, and can be launched more often. However, attitude control of a solar sailing CubeSat is challenging due to the low controllability of the CubeSat itself. In this paper, a new attitude control method for the solar sailing CubeSat where solar radiation pressure torque, which is a torque generated by the satellite's center of mass offset with respect to its center of pressure, is used as the controlling torque. In this study, a mechanical structure to adjust the center of mass with the CubeSat as a movable mass is presented. The CubeSat's position on the solar sail's surface plane can be adjusted to control the attitude about the roll and pitch axes. Therefore, a dynamics model for the solar sailing CubeSat is derived and an attitude controller is developed. The method is demonstrated for the case of a 10 × 10 m 2 sail with a 12-U CubeSat. The simulation results show that the solar sail attitude maneuver and sun pointing stability control are feasible when the initial and desired states satisfy the constraints. As a semi-active control method, the system can be combined with a micro flywheel control system for the attitude stability control of the CubeSat. Highlights: Semi-active control method with flywheel for CubeSat attitude stability control produced. CubeSat considered a movable mass that generates necessary amount of SRP control torque. New system can be used only as an auxiliary attitude control system at the present.